The evidence of radio polarization induced by the radiative grain alignment and self-scattering of dust grains in a protoplanetary disk - Kataoka, Akimasa; Pohl, Adriana (The astrophysical journal. Part 2, Letters, 2017)
The mechanisms causing millimeter-wave polarization in protoplanetary disks are under debate. To disentangle the polarization mechanisms, we observe the protoplanetary disk around HL Tau at 3.1 mm with the Atacama Large Millimeter/submillimeter Array (ALMA), which had the polarization detected with CARMA at 1.3 mm. We successfully detect the ring-like azimuthal polarized emission at 3.1 mm. This indicates that dust grains are aligned with the major axis being in the azimuthal direction, which is consistent with the theory of radiative alignment of elongated dust grains, where the major axis of dust grains is perpendicular to the radiation flux. Furthermore, the morphology of the polarization vectors at 3.1 mm is completely different from those at 1.3 mm. We interpret the polarization at 3.1 mm to be dominated by the grain alignment with the radiative flux producing azimuthal polarization vectors, while the self-scattering dominates at 1.3 mm and produces the polarization vectors parallel to the minor axis of the disk. By modeling the total polarization fraction with a single grain population model, the maximum grain size is constrained to be ##IMG## [http://ej.iop.org/images/2041-8205/844/1/L5/apjlaa7e33ieqn1.gif] $100\,μ \rmm$ , which is smaller than the previous predictions based on the spectral index between ALMA at 3 mm and the Very Large Array at 7 mm.